Potential of Mentha spicata L. Leaf Fraction Spray as an Antibacterial and Antiseptic Agent in an Infected Incision Wound Model: In Vitro and In Vivo Studies - Nabilla Putri Auliyah; Candra Eka Saputra; Aqilla Farhanadila; Riswanda Irsadina Najiha; Fadilla Citra Suci; Ani Florida Ngete (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Bacterial infections in incision wounds, predominantly caused by pathogens like Staphylococcus aureus and Pseudomonas aeruginosa, present a critical challenge in post operative care. Mentha spicata L. leaves, rich in carvone and limonene, possess substantial potential as natural antibacterial and wound healing agents. This study aimed to evaluate the physical stability of a 70% ethanol fraction spray formulation of Mentha spicata L. and its in vivo healing efficacy on a Staphylococcus aureus infected incision wound model. Initially, an in vitro antibacterial screening against Staphylococcus aureus and Pseudomonas aeruginosa was conducted using a 5% concentration of n-hexane, chloroform, and 70% ethanol fractions. The 70% ethanol fraction was determined as the optimal fraction against Staphylococcus aureus, exhibiting the highest diameter of zone of inhibition (DZH: 16.32 ± 0.31 mm), while Pseudomonas aeruginosa showed low sensitivity (5.26 ± 0.41mm) due to its robust biofilm barrier. This optimal fraction was formulated into a spray preparation at three concentrations: 5% (F1), 10% (F2), and 20% (F3). Stability testing through 3 consecutive cycles of a cycling test confirmed that all formulations remained physically and chemically stable. For the in vivo efficacy test, threee male New Zealand White rabbits received a 2 cm incision wound inoculated with 10⁸ CFU/mL of Staphylococcus aureus. The treatment efficacy was evaluated by measuring the relative wound area on Days 0, 7, and 14. Data were analyzed using Two Way ANOVA followed by a Post Hoc LSD test (p < 0.05). In vivo results indicated that F3 (20%) significantly accelerated incision wound closure compared to the Negative Control (p < 0.05), showing an identical healing progression to the commercial antiseptic Positive Control (p > 0.05). In conclusion, the 70% ethanol fraction spray of Mentha spicata L. leaves at 20% is stable and effective, making it a promising phytopharmaceutical candidate for treating infected incision wounds.